Design of Infiltration Well in Wetlands Area that Suitable for Giving Maximum Groundwater Recharge - Irfan Prasetia (Center for Journal Management and Publication, 2014)
Growth in residential, industrial, and officeÂ area,are significantly occurred in all city in Indonesia. Unfortunately, this is also caused more land that being covered by pavement and concrete in the cities. Realized or not it will disturb the availability of the groundwater and also lead to flooding in the rainy season. One of the effective solutions to solve this problem is by making sufficient numbers of infiltration well in the city, especially in the residential area. This research was conducted to analyze the ideal design of the infiltration well in the residential area. The design was made according to the equation by Sunjoto, which also refers to Indonesia standard (SNI) No: 03- 2453-2002. The results show that the ideal dimension for the infiltration well is to use the radius of the well (R) of 1.25 m. With the R of 1.25 will give a significant recharge to the groundwater as much as â‰ˆ 2.400 liter. It is expected that this research encourage a development in the urban drainage systems which will consider the environment and the groundwater reservation for the balance of our ecosystem.